Pembangunan Sumber Daya Manusia Menyongsong Era Globalisasi Di Kabupaten Jember: Human Resource Development in Facing the Era of Globalization in Jember Regency - Munif Widodo (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2002)
The critical phenomenon underpinning this research is the low quality of human resources in Jember Regency, indicated by the dominance of elementary school graduates (24.12%) and only 0.62% university graduates, alongside limited access to healthcare and skills training. Theoretically, human resource development is positioned as a key pillar of national development, aligned with the UNDP concept emphasising productivity, equity, sustainability, and empowerment. This study aims to examine the strategic efforts needed in education, health, and skills development to face the era of globalisation in Jember Regency. A qualitative descriptive method with a survey design was employed, involving respondents from BAPPEDA, district heads, village chiefs, and academics, using observation, questionnaires, documentation, and focus group discussions. The findings reveal that health services and formal education remain uneven, while skills training is not yet oriented towards labour market demands. In conclusion, improving human resource quality is urgent and requires demand-driven training reform, prioritised health interventions, and better linkage between education policies and employment needs. Fenomena krusial yang melatarbelakangi penelitian ini adalah rendahnya kualitas sumber daya manusia (SDM) di Kabupaten Jember, terindikasi dari dominasi lulusan SD (24,12%) dan hanya 0,62% lulusan S1, serta keterbatasan akses kesehatan dan keterampilan. Secara teoretis, pembangunan SDM diposisikan sebagai pilar utama pembangunan nasional, sejalan dengan konsep UNDP yang menekankan produktivitas, pemerataan, keberlanjutan, dan pemberdayaan. Penelitian ini bertujuan mengkaji upaya-upaya strategis yang diperlukan dalam pembangunan bidang pendidikan, kesehatan, dan keterampilan untuk menyongsong era globalisasi di Kabupaten Jember. Metode yang digunakan adalah penelitian deskriptif kualitatif dengan rancangan survei, melibatkan responden dari BAPPEDA, camat, kepala desa, dan akademisi, serta teknik observasi, kuesioner, dokumentasi, dan diskusi kelompok terfokus. Hasil penelitian menunjukkan bahwa layanan kesehatan dan pendidikan formal masih belum merata, sementara pelatihan keterampilan belum berorientasi pada kebutuhan dunia kerja. Kesimpulannya, peningkatan kualitas SDM mutlak dilakukan melalui reformasi pelatihan berbasis permintaan pasar kerja, dengan rekomendasi perlunya penajaman prioritas kesehatan dan penyelarasan kebijakan pendidikan dengan ketenagakerjaan.